Language, Culture and Emotions in Communication: Semiotic Dimension (Global Journal of Human-Social Science, 2023)
Language and culture are inseparable it is impossible for a language to exist that is not immersed in the context of culture and a culture that does not have a structure like a natural language in its center Within the framework of the study of the emotional sphere of a person in a crosscultural aspect a linguistic personality appears in such a significant image as Homo Sentiens or an emotional person Reflecting in language emotions acquire the status of emotiveness The results of the linguo-semiotic cross-cultural analysis are accumulated in the content of the invariant emotive-indicative field Generally linguo-semiotics including emotive semiotics occupies a central place in the family of sciences since without receiving storing and transmitting information human life is impossible including the dialogue of cultures
Keywords: homo sentiens; culture; language; semiotic system; cognition; emotions; invariant emotive-indicative field; emotive codes